2014
DOI: 10.1093/gji/ggu176
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocity structure in the Hot Springs and Trifurcation areas of the San Jacinto fault zone, California, from double-difference tomography

Abstract: We present tomographic images of crustal velocity structures in the complex Hot Springs and Trifurcation areas of the San Jacinto Fault Zone (SJFZ) based on double-difference inversions of earthquake arrival times. We invert for V P , V S and hypocentre location within 50 × 50 × 20 km 3 volumes, using 266 969 P and 148 249 S arrival times. We obtain high-fidelity images of seismic velocities with resolution on the order of a few kilometres from 2 to 12 km depth and validate the results using checkerboard tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 100 publications
14
91
1
Order By: Relevance
“…Using a dislocation model in a heterogeneous elastic half space, Lindsey et al (2014) have shown that a reduction in shear modulus within the FZ by a factor of 2.4 is required to fully explain the observed strain rate along the SJFZ, assuming a 15-km locking depth. Such reduction in elastic modulus and thus in seismic velocities is much higher than as imaged by regional seismic tomography (Allam and Ben-Zion 2012; Allam et al 2014a). However, a similar magnitude of reduction in elastic modulus to the seismically determined value will result in a locking depth of 10 km, much shallower than the observed 14-18 km depth of seismicity along the SJFZ (Lindsey et al 2014).…”
Section: Gps Datamentioning
confidence: 88%
“…Using a dislocation model in a heterogeneous elastic half space, Lindsey et al (2014) have shown that a reduction in shear modulus within the FZ by a factor of 2.4 is required to fully explain the observed strain rate along the SJFZ, assuming a 15-km locking depth. Such reduction in elastic modulus and thus in seismic velocities is much higher than as imaged by regional seismic tomography (Allam and Ben-Zion 2012; Allam et al 2014a). However, a similar magnitude of reduction in elastic modulus to the seismically determined value will result in a locking depth of 10 km, much shallower than the observed 14-18 km depth of seismicity along the SJFZ (Lindsey et al 2014).…”
Section: Gps Datamentioning
confidence: 88%
“…As was mentioned previously, the regression-based results represent an apparent modulus; hence, the true reductions in modulus are likely multiple orders of magnitude smaller than those seen in Figure 10, for example. But in consideration of recent tomographic imaging [Allam and Ben-Zion, 2012;Allam et al, 2014], observations from dense seismic array deployments [Zigone et al, 2014], space geodetic studies , inferences from poroelastic modeling [Barbour and Wyatt, 2014], and the data presented here, it is highly likely that significant reductions in modulus are ubiquitous around the San Jacinto Fault. More work is needed, though, to firmly establish the magnitudes and spatial extent and of these reductions.…”
Section: Effects Of Faulting In Responsementioning
confidence: 91%
“…In addition, data availability and recent methodological advances allow for dramatically improved 3D seismic imaging results. Hundreds of stations and tens of thousands of events distributed throughout the study area provide ample volumetric sampling for highresolution tomographic methods which have previously been applied to image fault and regional structure elsewhere (e.g., Thurber, 2003, Allam andBennington et al, 2013;Allam et al, 2014a). Migration of receiver functions using accurate 3D seismic velocity models has been shown to change interpretations (Gilbert, 2012;Hansen et al, 2013;Ozakin & Ben-Zion, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Following previous applications (Zhang & Thurber 2003;Thurber et al, 2006;Allam & Ben-Zion, 2012;Allam et al, 2014a), we perform 35 iterations with a progressive weighting scheme between absolute and differential arrival time data. In the first few iterations, the absolute arrival time data are weighted more importantly by a factor of 10.…”
Section: Double-difference Tomographymentioning
confidence: 99%